Adobe's Acrobat -- providing the missing link? - Brailsford, David F. (Mecklermedia, 1994)
Adobe's Acrobat software, released in June 1993, is based around a new Portable Document Format (PDF) which offers the possibility of being able to view and exchange electronic documents, independent of the originating software, across a wide variety of supported hardware platforms (PC, Macintosh, Sun UNIX etc.). The fact that the imageable objects are rendered with full use of Level 2 PostScript means that the most demanding requirements can be met in terms of high-quality typography, device-independent colour and full page fidelity with respect to the printed version. PDF possesses an internal structure which supports hypertextual features, and a range of file compression options. In a sense PDF establishes a low-level multiplatform machine code for imageable objects but its notion of hypertext buttons and links is similarly low-level , in that they are anchored to physical locations on xed pages. However, many other hypertext systems think of links as potentially spanning multiple files, which may in turn be located on various machines scattered across the Internet. The immediate challenge is to bridge the "abstraction gap" between high-level notions of a link and PDF's positionally-anchored low-level view. More specifically, how can Mosaic, WWW and Acrobat/PDF be configured so that the notions of "link ", in the various systems, work together harmoniously? This paper reviews progress so far on the CAJUN project (CD-ROM Acrobat Journals Using Networks) with particular reference to experiments that have already taken place in disseminating PDF via e-mail, Gopher and FTP. The prospects for integrating Acrobat seamlessly with WWW are then discussed.